2019
DOI: 10.1371/journal.pone.0210260
|View full text |Cite
|
Sign up to set email alerts
|

Can Kinect aid motor learning in sportsmen? A study for three standing techniques in judo

Abstract: Our objective was to examine how exercises with the second generation of the Microsoft Kinect sensor may aid in the process of motor learning in young judo practitioners. We addressed improvements in spatio-temporal accuracy during execution of three standing techniques in judo, in a simple paradigm designed to study short-term practice effects. Two groups of judokas, 12 athletes each—one aided with Kinect and our dedicated software vs a group of controls—were asked to mimic previously recorded master-level pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…The article [13] investigates the effect of using the MS Kinect camera to assist young judokas' motor training by simulating pre-recorded performances of three master-level techniques.…”
Section: Source: Compiled By the Authorsmentioning
confidence: 99%
“…The article [13] investigates the effect of using the MS Kinect camera to assist young judokas' motor training by simulating pre-recorded performances of three master-level techniques.…”
Section: Source: Compiled By the Authorsmentioning
confidence: 99%
“…A promising way to support the embodiment of simulations of action in depressed individuals is by using remote kinematics in the form of exergaming (XboxKinect™ games). Previous research showed that using exergaming results in the augmentation of motor (kinesthetic) imagery [26][27][28], increased motor rehabilitation in stroke patients [29], motor learning [30] and it is efficient as a stand-alone intervention for the reduction of depressive symptomatology [31][32][33][34]. Furthermore, exergaming has an increased acceptability and feasibility in various populations [29].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that using exergaming results in the augmentation of motor (kinesthetic) imagery (Wriessnegger et al, 2014(Wriessnegger et al, , 2018(Wriessnegger et al, , 2020, increased motor rehabilitation in stroke patients (Almasi et al, 2022), motor learning (Sielużycki et al, 2019) and it is efficient as a stand-alone intervention for the reduction of depressive symptomatology (Abd-Alrazaq et al, 2022;Huang et al, 2022;Rica et al, 2020;Yunus et al, 2020).…”
mentioning
confidence: 99%